FEATURES OF THE LONG-TERM USE OF THE DRUG NIMESULIDE (NIMESIL) - Muxsinova Shaxlo Mulximovna; Abdiraxmanov Resul (Web of Journals Publishing, 2025)
At present, effective pain relief is one of the most important tasks of modern society. Since inflammation is the main cause of the development of acute and chronic pain, non-steroidal anti-inflammatory drugs are most often used in the treatment of rheumatic diseases. To effectively help patients with rheumatic diseases, it is necessary to choose a drug that has a pronounced therapeutic effect from the group of non-steroids, is in demand for rapid development of the effect and good safety. The drug nimesulide (Nimesil) has this property. Non-steroidal anti-inflammatory drugs are used in short courses until pain syndrome and local inflammation decrease, but in patients with persistent activity and signs of the disease, long-term use of these drugs is necessary. When prescribing these drugs for the long term, it is necessary to take into account the risk of cardiovascular, gastrointestinal and kidney pathologies.
Keywords: Nimesulide, nimesil, Syclo-oxygenase -1, cyclo-oxygenase-2 inhibitors, prostaglandin, proton pump inhibitors, hepatotoxic, nephrotoxic effects.